Effects of in vitro simulated digestion on the α-glucosidase inhibitory activity, structure, and prebiotic activity of a polysaccharide from Anemarrhena asphodeloides Bunge - Li, Baolian; Fang, Guihong; Lan, Meijuan; Xiao, Juan; Zhang, Xia; Li, Lin; Li, Bing; Chen, Juncheng (Frontiers in Nutrition, 2025)
This study explored the changes in the structure and α-glucosidase inhibitory activity of a non-starch polysaccharide derived from Anemarrhena asphodeloides Bunge, AABP-1B, during digestion in vitro and its effect on host intestinal microbiota. Simulations of digestion in the upper digestive tract showed that the reducing sugar content and molecular weight of AABP-1B changed slightly, though no monosaccharides were detected. AABP-1B was resistant to degradation in the simulated upper gastrointestinal environments, retained strong α-glucosidase inhibitory activity after digestion, which may be related to the lack of structural changes. In in vitro fermentation, AABP-1B enhanced the growth of commensal microorganisms, including Bacteroides, Megasphaera, and Prevotella, while inhibiting the proliferation of pathogenic bacteria, such as Escherichia-Shigella. Fermentation of AABP-1B by gut microbes resulted in a notable increase in short-chain fatty acid contents and a decrease in pH levels. Our findings showed that AABP-1B promotes intestinal health and may serve as a prebiotic in the development of functional food.